Implementatıon Of Sıx Sıgma To Improve Delınquent Borrowers Desk Collectıon Dıvısıon AT PT XYZ - Rina Febrizi Hasibuan; Rosalendro Eddy Nugroho (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Problems faced by the Desk Collection division at PT. XYZ is the number of consumers who experience late payments on agreed loans. This research aims to find out the causes of late payments by consumers, strategies for implementing improvements so that consumers pay back on time and find out what achievement (success rate) is obtained after repairs. Improvement efforts were made by implementing Six Sigma through the DMAIC stages, namely Define, Measure, Analysis, Improve and Control using Pareto diagrams, Fishbone Analysis, Why Analysis and 5W+1H to identify the root of the problem and make improvements to the problem. The research results obtained by implementing Six Sigma were that the root of the problem and the strategy for implementing improvements were obtained so that an increase in payment achievement (success rate) was obtained, namely from 66% before the improvement to 71% after the improvement, or an increase of 5%. Through the implementation strategy of the improvements made, it is hoped that PT. XYZ.